Implementing a Manualized, Classroom Transition Intervention for Students With ASD in Underresourced Schools. Issue 1 (January 2018) - Iadarola, Suzannah; Shih, Wendy; Dean, Michelle; Blanch, Erica; Harwood, Robin; Hetherington, Susan; Mandell, David; Kasari, Connie; Smith, Tristram
Children with autism spectrum disorder (ASD) in public education settings experience difficulties with transitions during classroom routines, which can result in challenging behavior. Single-subject research supports techniques for transitions, but school-based approaches often require resources and training unavailable in low-resource districts, limiting implementation. We developed and evaluated the Schedules, Tools, and Activities for Transitions (STAT) program, a short-term, manualized intervention of behavioral supports to support daily routine transitions for students with ASD (K-5) in underresourced districts. We utilized a multisite, cluster-randomized, group comparison design (immediate treatment versus waitlist) with matched pairs ( n = 150 students, 57 educators). Data indicated (a) no group differences for academic engagement or classroom independence, and (b) an advantage for STAT in reducing challenging behavior and increasing teacher fidelity. Results show preliminary support for an intervention that is feasible and perceived as sustainable in real-world settings.